APLIKASI EDUKASI MATA PELAJARAN ILMU PENGETAHUAN ALAM BERBASIS ANDROID - Hutapea, Indra; Koko Handoko (Computer Science and Industrial Engineering, 2024)
Education according to the law concerning the National Education System No. 20 of 2003 Article 37 Paragraph 1 That the primary and secondary education curriculum must contain natural science (IPA). Natural science study materials are intended to develop students' knowledge, understanding and analytical skills of the natural environment and its surroundings. The scope of science includes aspects of living things, objects, energy, earth and nature. The RAD method is a method that focuses on developing applications quickly through iterative development and feedback, in accordance with the target of a shorter application development time. At present, with increasingly high and advanced technological developments, the use of Android smartphones in education is still less visible in the activities that students tend to do on social media and games so that the available time is not utilized properly, Some schools still use the old method, namely only using books, especially regarding the use of teaching materials and implementation of learning, teaching materials have an influence on students. With the problems that exist at this location, what is offered in this research is to build a system with research results in the form of an Android-based application for natural science subjects.